The Mediating Effect of Facilitating Conditions on The Relationship Between Actual Usage of Online Social Networks (OSN) And User Satisfaction - Almarri , Hamad; Ameen , Ali; Bhaumik, Amiya; Alrajawy, Ibrahim; Khalifa, Gamal S. A. (International Journal of Psychosocial Rehabilitation, 2020)
The rapid rate of change in the organization's environment has continuously pushed the need for technologies and acceptance of these technologies at an accelerating rate. The new technologies are enabling organizations to be flatter, networked, and more flexible. Organizations in the 21st century inevitably make substantial investments in Information Technology (IT) in order to achieve competitive advantage, by spending enormous sums of money on computer hardware, software, communication networks, databases and specialized personnel. The main objective of this study is to determine factors influencing the user satisfaction of online social networks use among employees within Tourism Development and Investment Company (TDIC) in Abu Dhabi. This study collected data through quota nonprobability sampling, and 401 valid responses were received. Structural Equation Modelling- Variance based (SEM-VB) through partial least squares (PLS) method to analyse the research model using the software of SmartPLS 3.0. Although various limitations exist, the findings have been encouraging, as it has managed to shed some lights on new variables affecting the user satisfaction of online social networks. This study proposed an extended model of the Unified Theory of Acceptance & use of Technology (UTAUT) and found that two variables play an important role to determine the performance impact of online social networks namely actual usage and facilitating condition. The findings of this study can provide policymakers with important insights on how to more successfully incorporate online social networks to improve performance and the services of public sector, and how to encourage top managers to ensure that employees are more likely to utilize new technologies and thereby enabling better work outcome, wider reach of services, gives employees more control over their daily tasks and enhances their performance.